2020
DOI: 10.3390/chemengineering4030047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Emulsifier System on Breakup and Coalescence of Oil Droplets during Atomization of Oil-In-Water Emulsions

Abstract: Spray drying of whey protein-based emulsions is a common task in food engineering. Lipophilic, low molecular weight emulsifiers including lecithin, citrem, and mono- and diglycerides, are commonly added to the formulations, as they are expected to improve the processing and shelf life stability of the products. During the atomization step of spray drying, the emulsions are subjected to high stresses, which can lead to breakup and subsequent coalescence of the oil droplets. The extent of these phenomena is expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Previous studies suggested single-droplet experiments as an additional tool to evaluate the stability of formulations with more than one surfactant against coalescence [17][18][19][20][21]. The general idea is the simplification of a double emulsion to a measurement setup where it can be distinguished between different instability mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested single-droplet experiments as an additional tool to evaluate the stability of formulations with more than one surfactant against coalescence [17][18][19][20][21]. The general idea is the simplification of a double emulsion to a measurement setup where it can be distinguished between different instability mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…When the coalescences times are too short (<1 s) the determination of the moment of contact is not accurate enough to achieve a reasonable measurement. When the coalescence times are too long (>30 min) the necessary repetitions of the measurement become very time consuming, or there is no coalescence observed at all within a defined maximum measurement time [19,22,23]. The coalescence time increases on a logarithmic rather than on a linear scale when increasing the concentration or changing the surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the oil droplets after atomization are evidently larger compared to the oil droplets after atomization with the other emulsifier systems. In our previous study, we demonstrated that these large oil droplets are the result of droplet coalescence directly after oil droplet breakup during atomization (Taboada et al, 2020). When considering the ODSD of the emulsion after spray drying it can be seen that the proportion of small droplets is reduced compared to the ODSD after atomization, with the smallest oil droplets being around 0.4 µm.…”
Section: Oil Droplet Size After Atomization and Spray Dryingmentioning
confidence: 91%
“…Oil-in-water emulsions were prepared for the investigations. Emulsions were prepared following the procedure described in (Taboada et al, 2020). Briefly, emulsion premixes (50 wt.% oil) consisting of an aqueous WPI solution and MCT oil with LMWE (lecithin or citrem or MoDi) were prepared and homogenized in a colloid mill (IKA magic LAB, IKA-Werke GmbH & Co. KG, Staufen, Germany) operated at a gap width of 0.16 mm and a circumferential speed of 26 m/s.…”
Section: Model Emulsions: Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation